Formação continuada das professoras da educação infantil: ações do município de Montes Claros / MG - Regina Coele Cordeiro (2018)
This dissertation had as objective to analyze the actions of continuous formation of the Municipal Secretary of Education (SME) of Montes Claros destined to the teachers of the Infantile Education in the administrative management 2013-2016. The paper describes and analyzes the actions of the SME, as well as the meanings attributed by the teachers and supervisors who work in Early Childhood Education (EI). In order to gather the information needed for the research, qualitative research strategies were used: consultation of documents produced by the Municipality of Montes Claros and the Municipal Education System (SME), as well as semistructured interviews. These were initially carried out with 3 managers (EI coordinator, educational analyst and in charge of the field education sector) who work in the Municipal Education Department. These resources were used with the intention of characterizing Early Childhood Education in the municipality, as well as identifying the continuing education actions offered to Early Childhood Education teachers. In addition to the managers, supervisors and teachers were also interviewed who work in the Children's Education Institutions of the municipality, aiming to understand the meanings that these professionals attribute to the offered formations. For this selection, we sought to cover the activities in the urban and rural areas, in the types of institutions (EI Municipal Center, municipal schools and contracted schools) and sub-bands - nursery and pre-school. We interviewed 13 teachers - 9 working in the urban area and 4 in the rural area - and 11 supervisors - 8 working in the urban area and 3 in the rural area. Through the research, the presence of three SME actions that directly or indirectly influenced the teachers' training was identified in the 2013-2016 management: the hiring of a company to provide consulting services, the legalization of a specific workload for the continued formation of the teachers - called Complementary Activities (AC) - and the contracting of a Teaching Teaching System. The results indicate that the training actions associated with practices and instruments aimed at the organization and systematization of the work of supervisors and teachers of Early Childhood Education have led to a reduction in the autonomy of these subjects, revealing the implementation of a technical-instrumental logic. In addition, these actions led, in the evaluation of the teachers, to intensify work by including tasks not directly related to working with children.